Reliability and Validity of a Treatment Barriers Scale for Individuals With Alcohol Use Disorder. (23rd February 2016) - Possemato, Kyle; Funderburk, Jennifer; Spinola, Suzanne; Hutchison, Dezarie; Maisto, Stephen A.; Lantinga, Larry J.; Oslin, David W.
ABSTRACT: Background : Few studies have measured addiction-specific barriers to treatment. A measurement of barriers with psychometric support that has been tested in diverse samples and that assesses multiple components of addiction treatment barriers is needed to inform providers and treatment programs. Objectives : This paper aims to provide an initial psychometric investigation of a measure of barriers to seeking addictions treatment. Methods : Data were collected from 196 Veterans Affairs primary care patients with Alcohol Use Disorder that participated in a randomized clinical trial. Results : A Principal Components Analysis revealed that the 32-item Treatment Barriers Scale (TBS) can be reduced to 14 items, measuring 4 factors: stigma, dislike of the treatment process, alcohol problem identification, and logistical concerns. Acceptable internal consistent reliability (α = .64–.76) and excellent precision of alpha (α = 0.001–0.009) was found for each subscale. Support for the measure's concurrent validity was found, for example, participants who reported more motivation to reduce their drinking perceived significantly fewer barriers to care. Support for the measure's predictive validity was also found, including that more barriers were related to future drinking among all participants and less mental health and addictions treatment visits among participants in one treatment condition. Conclusions/ Importance : Our results provide initial support for the utility of the TBS-14 among primary care patients with Alcohol Use Disorder. Use of the TBS-14 could enable healthcare providers to better understand patient-specific treatment barriers, provide corrective information on treatment misconceptions, and inform individualized treatment plans that increase patient engagement in addiction services.